Assessment of Hepatocellular Carcinoma Metastasis Glycobiomarkers Using Advanced Quantitative N-glycoproteome Analysis - Liu, Tianhua; Shang, Shuxin; Li, Wei; Qin, Xue; Sun, Lu; Zhang, Shu; Liu, Yinkun (Frontiers in Physiology, 2017)
Hepatocelluar carcinoma (HCC) is one of the most common malignant tumors with high incidence of metastasis. Glycosylation is involved in fundamental molecular and cell biology process occurring in cancer including metastasis formation. In this study, lectin microarray, lectin blotting, lectin affinity chromatography and tandem 18O stable isotope labeling coupled with liquid chromatography-mass spectrometer (LC-MS) analysis were applied to quantify the changes in N-glycosite occupancy for HCC metastasis serum. Firstly, lectin microarray was used to screen glycoforms and Phaseolus vulgaris Leucoagglutinin (PHA-L) reactive structure (β1,6-GlcNAc branched N-glycan) was found to be increased significantly in HCC patients with metastasis compared with those with non-metastasis. Then, PHA-L affinity glycoproteins were enriched followed by N-glycosite occupancy measurement with strategy of tandem 18O stable isotope labeling. 11 glycoproteins with significantly changed N-glycosite occupancy were identified, they were associated with cell migration, invasion and adhesion through p38 mitogen-activated protein kinase signaling pathway and nuclear factor kappa B signaling pathway. Quantification of N-glycosite occupancy for PHA-L reactive glycoproteins could help to discover important glycoproteins of potential clinically significance in terms of HCC etiology. Also, understanding of N-glycosite occupancy alterations will aid the characterization of molecular mechanism of HCC metastasis as well as establishment of novel glycobiomarkers.